Studies of protein-ligand interactions by NMR. - Clarkson, J; Campbell, I (2003)
Solution-state NMR has become an accepted method for studying the structure of small proteins in solution. This has resulted in over 3000 NMR-based co-ordinate sets being deposited in the Protein Databank. It is becoming increasingly apparent, however, that NMR is also a very powerful tool for accessing interactions between macromolecules and various ligands. These interactions can be assessed at a wide variety of levels, e.g. qualitative screening of libraries of pharmaceuticals and 'chemical shift mapping'. Dissociation constants can sometimes be obtained in such cases. Another example would be the complete three-dimensional structure determination of a protein-ligand complex. Here we briefly describe a few of the principles involved and illustrate the method with recent examples.